The Gold-Mines of the San Pedro District, Cerro de San Pedro, State of San Luis Potosi, Mexico - George A. Laird (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
I. INTRODUCTION. THIS old and once famous district played, through its enormous production of silver and gold, an important part in the history of the State of San Luis Potosi. According to a pamphlet prepared under the direction of the Governor of the State, Sr. Don Blas Escontria, and presented to the visiting members of the Institute during the Mexican meeting of 1901, this district is situated 20 km. east of the city of San Luis Potosi, in a range of mountains of moderate height, extending 135 km. N. and S., and 16 km. E. and W.; and the mineralized area hitherto developed is about 600,000 sq. m. The history of the district,. as given by the record dated 1778, and formerly kept in the San Francisco convent, says that it was discovered in 1575 by Sr. Don Pedro Irarte, and adds that the city of San Luis Rey de Francisco del Potosi received its name (in allusion to the famous Potosi mines in Bolivia) by reason of the remarkable productiveness of its gold- and silver-mines in the first period of their exploration, during which they paid to the Crown, as " quintos " (the fifth part of the product), $97,000,000, as appears from the accounts of the royal treasury. The amount of the quientos paid during the " bonanza period " of 80 years was $72,000,000. The larger sum first mentioned probably represents a longer series of years. But either will suffice to indicate the great wealth of the mines. In 1663, the decadence of the industry began with the caving¬ in of several mines, concerning which the record of 1778, al¬ready cited, says, in substance, that on Good Friday one of the owners in the enterprise, in view of the unfavorable prospect of a lawsuit in which he was engaged, set fire to the timbers supporting the underground galleries and workings of the San